"If relatives inherited the gene, they should inherit the data." Bringing the family into the room where bioethics happens. Issue 1 (2nd January 2022) - Gordon, Deborah R.; Koenig, Barbara A.
Abstract : Biological kin share up to half of their genetic material, including predisposition to disease. Thus, variants of clinical significance identified in each individual's genome can implicate an exponential number of relatives at potential risk. This has renewed the dilemma over family access to research participant's genetic results, since prevailing US practices treat these as private, controlled by the individual. These individual-based ethics contrast with the family-based ethics – in which genetic information, privacy, and autonomy are considered to be familial – endorsed in UK genomic medicine and by participants in a multi-method study of US research participants presented here. The dilemma reflects a conflict between US legal and ethical frameworks that privilege "the individual" and exclude "the family" versus actual human genetics that are simultaneously individual and familial. Can human genetics succeed in challenging bioethics' hegemonic individualism to recognize and place the family at the center of the room where bioethics happens?